Policy Development Model of Independent Village in the Region Rasau Jaya District Kubu Raya Regency - Martoyo, Martoyo; Yulius Yohanes; Isdairi, Isdairi; Martinus, Martinus; Abdul Rahim (Cita konsultindo, 2024)
This research is entitled Independent Village Policy Development Model in Rasau Jaya District, Kubu Raya Regency, which aims to construct an independent village development model in Rasau Jaya District, Kubu Raya Regency. This research is motivated by the problems of poverty, welfare, and community empowerment in six villages in Rasau Jaya District (General Rasau Jaya Village, Rasau Jaya Satu Village, Rasau Jaya Dua Village, Rasau Jaya Tiga, Bintang Mas Village, and Pematang Seven Village), while in the Building Village Index (IDM) the six villages have been included in the independent village category in 2023. This is certainly a special concern in the implementation of independent villages and the need for strategic steps to maintain and improve the development of the social composite index (IKS), economic composite index (IKE) and environmental composite index (IKL) in the village with village empowerment programs or policies. In order to determine the implementation of development in six villages in Rasau Jaya District, this research was conducted by qualitative descriptive analysis. The results of this study show that the social composite index needs efforts to improve the condition of the poor, IKE has the potential for plantations, agriculture and animal husbandry to be an important sector in supporting the economy of the people of Rasau Jaya District, and IKL becomes a polemic is that forest fires still often occur in Rasau Jaya District and the community's water needs are a problem for the environment. Researchers recommend the need for policies to maintain the Status of Independent Villages in Rasau Jaya District by involving the government, private sector, community and academics in preparing strategic village policy plans in Rasau Jaya District, Kubu Raya Regency. Keywords: Policy, Development, Empowerment, Independent Village.